Dynamic spatio-temporal contribution of single β5t+ cortical epithelial precursors to the thymus medulla - Mayer, C; Žuklys, S; Zhanybekova, S; Ohigashi, I; Teh, H; Sansom, S; Shikama-Dorn, N; Hafen, K; Macaulay, I; Deadman, M; Ponting, C; Takahama, Y; et al. (Wiley, 2016)
Intrathymic T-cell development is critically dependent on cortical and medullary thymic epithelial cells (TECs). Both epithelial subsets originate during early thymus organogenesis from progenitor cells that express the thymoproteasome subunit β5t, a typical feature of cortical TECs. Using in vivo lineage fate mapping, we demonstrate in mice that β5t(+) TEC progenitors give rise to the medullary TEC compartment early in life but significantly limit their contribution once the medulla has completely formed. Lineage-tracing studies at single cell resolution demonstrate for young mice that the postnatal medulla is expanded from individual β5t(+) cortical progenitors located at the cortico-medullary junction. These results therefore not only define a developmental window during which the expansion of medulla is efficiently enabled by progenitors resident in the thymic cortex, but also reveal the spatio-temporal dynamics that control the growth of the thymic medulla.